Determinants of Audit Delay: The Moderating Role of Firm Size in Conventional Commercial Bank in Indonesia and Singapore (2021-2025) - Singa, Henita Guru; Erlina, Erlina; Nasution, Abdillah Arif (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study investigates the effects of audit fee, audit committee, and firm age on audit delay, with firm size serving as a moderating variable in conventional commercial banks in Indonesia and Singapore during the 2021–2025 period. A quantitative approach with a causal-associative design was employed. The population consisted of conventional commercial banks listed on the Indonesia Stock Exchange (IDX) and commercial banks operating under the Monetary Authority of Singapore (MAS). The sample was selected using purposive sampling, and secondary data were collected from audited annual financial statements. Panel data regression analysis was used to test the proposed hypotheses. The findings indicate that audit fee and firm age do not have a significant effect on audit delay. In contrast, the audit committee significantly affects audit delay, suggesting that effective oversight and monitoring contribute to a more timely audit completion process. Simultaneously, audit fee, audit committee, and firm age significantly influence audit delay. The moderation analysis further reveals that firm size moderates the relationship between firm age and audit delay, indicating that larger and more established banks tend to complete audits more efficiently. However, firm size does not moderate the relationships between audit fee and audit delay or between audit committee and audit delay. Overall, the results highlight the importance of audit committee effectiveness and organizational capacity in enhancing audit timeliness within the banking industry.